THE STUDY EXAMINES THE CORRELATION BETWEEN PATIENT CONDUCT AND THE PREVALENCE OF TYPE I AND TYPE II HYPERTENSION AT SUBULUSSALAM CITY HOSPITAL 2023 - Leni Rahayu; Susy Sriwahyuni; Safrizal; Perry Boy Chandra Siahaan; Fikri Faidul Jihad (PT. Radja Intercontinental Publishing, 2024)
diseases. In the context of research on hypertension, it can be interpreted that this condition occurs when blood pressure indicates more than 140/90 mmHg and 180/120 mmHg. cases of hypertension in 2023 were 555 patients. This data is also supported by the initial survey of research, where patients often do poor activities due to a lack of knowledge. Research Objectives: to determine the relationship between knowledge, attitudes, and actions of hypertensive patients at Subulussalam City Hospital. The type of research used is quantitative research with an observational analytic method and a cross-sectional study design conducted on December 29, 2023, at Subulussalam City Hospital with a sample size of 233 respondents calculated using the Slovin formula. Sample withdrawal was done using the accidental sampling technique. Data collection was done through interviews using a questionnaire. The results of this study indicate a significant relationship between knowledge and (p value = 0.001 PR = 2.279), attitude (p value = 0.000 PR = 3.737), and action (p value = 0.001 PR = 2.279). It is necessary to continue health promotion programs in the prevention of hypertension using both counseling and empowerment methods so as to achieve the goal of changing behavior, especially community action in the prevention of hypertension. Patients can change their diet and do physical activities such as regular exercise, not smoking, and screening blood pressure checks.